Chemical and Physical Determination of Gibberellic Acid Effects on Postharvest Quality of Sweet Cherry. - OZKAYA, OKAN; DUNDAR, OMUR (Asian Journal of Chemistry, 2010)
The effect of preharvest gibberellic acid treatments with the dose of 10, 20 and 30 ppm on Aksehir Napolyon sweet cherry were compared with control during 4 weeks storage. The most important problem of sweet cherry is decolouration of stem after storage. Different preharvest treatments can be effective to stop or slow down decolouration. In this research fruit firmness, titrable acidity, total soluble solids, stem colour (1-3 scale), weight losses and fruit decay were evaluated depend on different concentrations of gibberellic acid. The application of gibberellic acid decreased the loss of fruit firmness, delayed stem decolouration and maintained the brightness during storage compared with control and the other application rates.